2018
DOI: 10.1007/s12016-018-8689-9
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Disorders Associated with Primary Immunodeficiency Diseases

Abstract: There are now 354 inborn errors of immunity (primary immunodeficiency diseases (PIDDs)) with 344 distinct molecular etiologies reported according to the International Union of Immunological Sciences (IUIS) (Clin Gastroenterol Hepatol 11: p. 1050-63, 2013, Semin Gastrointest Dis 8: p. 22-32, 1997, J Clin Immunol 38: p. 96-128, 2018). Using the IUIS document as a reference and cross-checking PubMed ( www.ncbi.nlm.nih.pubmed.gov ), we found that approximately one third of the 354 diseases of impaired immunity hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 201 publications
2
23
0
1
Order By: Relevance
“…We hypothesized that weighted diagnosis codes and pharmacy records may inform individual risk for PI across a population and could therefore be utilized as a clinical decision aid during routine patient care. This is important because the presentation of PI is variable and recognition of the disease entity can be challenging (19). Also, among patients with immune deficiency, annual disease-related care exceeds $100,000 and post-diagnosis cost savings are calculated to be $78,166 (USD) even when cost of therapy is accounted for (15, 16, 20).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that weighted diagnosis codes and pharmacy records may inform individual risk for PI across a population and could therefore be utilized as a clinical decision aid during routine patient care. This is important because the presentation of PI is variable and recognition of the disease entity can be challenging (19). Also, among patients with immune deficiency, annual disease-related care exceeds $100,000 and post-diagnosis cost savings are calculated to be $78,166 (USD) even when cost of therapy is accounted for (15, 16, 20).…”
Section: Introductionmentioning
confidence: 99%
“…According to Malamut et al, villous atrophy was observed in over 50% of CVID patients [ 156 ], while Luizi et al indicated it to be 31.2% [ 221 ]. A literature review performed by Hartono et al reported the presence of villus atrophy in CVID patients within the range of 24% to 50% [ 222 ]. However, Karaca et al showed a lower incidence of celiac-resembling enteropathy in CVID, as it affected only 10% of the study participants [ 92 ].…”
Section: Celiac Disease In Common Variable Immunodeficiencymentioning
confidence: 99%
“…Histological findings in coexistent SIgAD and UC or CD are consistent with those concerning UC or CD separately, which are described above [ 8 , 287 ]. Despite this, many authors underline the need of ruling out PID in patients with IBD and a consistent history of recurrent infection, failure to respond to therapy, or a particularly severe course of disease [ 14 , 15 , 222 ].…”
Section: Inflammatory Bowel Disease In Selective Iga Deficiencymentioning
confidence: 99%
See 2 more Smart Citations